Return Migration and Entrepreneurship in Egypt - Fouda, Shorouk (AUC Knowledge Fountain, 2021)
Many Egyptians are currently choosing to emigrate in pursuit of benefits such as; education, professional development, acquisition of new skills and accumulation of savings. Although this was previously viewed as having a damaging effect to a country’s economy through the loss of most talented and ambitious nationals, more pertinent economic views suggest possible instances of brain circulation and gain upon the return of a national to their home country. In some cases, gains of return migration are unlocked in the form of entrepreneurial behavior; as a result of accumulation of financial and human capital. In this research, both quantitative and qualitative methods were employed to test the relation between return migration and entrepreneurship. Data from the Egyptian Labor Market Panel Survey 2018 was analyzed to test the relationship between savings and entrepreneurial potential. In addition, in depth interviews were conducted with 31 current and return migrants in order to test the relationship between human capital acquisition and the potential to engage in entrepreneurial activities upon return. The researcher found emigrants to have accumulated human capital abroad that they could have not acquired otherwise. Although most of the interviewees expressed interest towards entrepreneurship, only a minority mentioned entrepreneurial activity as one of their return plans. The research presents a variety of recommendations for utilizing skills acquired abroad in successful ventures; such as: hosting entrepreneurship boot camps, launching hubs for startups, assigning business coaches for return migrants and designing occupational building programs.